ARE BIOMEDICINE HEALTH PRACTITIONERS READY TO COLLABORATE WITH TRADITIONAL HEALTH PRACTITIONERS IN HIV AND AIDS CARE IN TUTUME SUB DISTRICT, BOTSWANA - Madiba, Sphiwe (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
The aim of this study was to determine BHPs’ views on collaboration with THPs in Tutume sub district, identify collaboration activities that have been going on and determine approaches to collaboration that are acceptable to BHPs. A cross sectional survey was conducted with a convenient sample of 60 biomedicine health practitioners. The sample was drawn from two primary hospitals and clinics in Tutume Sub-District, Botswana. A pre-tested self administered questionnaire with open- and closed ended questions was used to obtain information. Majority of BHPs were in favour of collaboration despite the low levels of collaboration with THPs and low levels of awareness of the policy on collaboration. Patient referral was the preferred approach to collaboration but majority of BHPs would not refer patients to THPs. Despite the fact that BHPs were not familiar with most traditional practices they were of the opinion that they will not learn anything from THPs but were favourable towards exchange of information and biomedical skills. We conclude that BHPs were not ready to collaborate with THPs in HIV and AIDS care. BHPs wanted collaboration to be on their terms i.e. they prefer the collaboration to be limited to one way referrals from TPHs to BHPs, they will teach THPs but they were not willing to learn from them and they had negative opinions of the traditional health practice. Therefore, lack of specific guidelines on collaboration negatively affected collaborative efforts in the sub-district.